THE USE OF CODE-SWITCHING TO SHOW EMPATHY IN BREAKOUT MUSIC PROGRAM ON NET TV - Nia Nella Ombuh; Muhammad Adam; Waladdin Panggabean (Faculty of Letters Universitas Balikpapan, 2019)
This research aims to find the use of code-switching to show empathy. There are two objectives of this research; 1) to identify the types of code-switching used in Breakout Music Program on NET TV and 2) to describe how code-switching shows empathy in Breakout Music Program on NET TV. The theories used in this study are; the types of code-switching by Romaine to answer the research question number one, and the reason to do code-switching by Hoffman to answer the research question number two. Based on the result of this research, the researcher found that all types of code-switching proposed by Romaine are found in Breakout music program. Furthermore, all seven reasons in using code-switching are also found in Breakout music program, however the most dominant reason for doing code-switching is to show empathy and the least dominant reason is to quote somebody else.